EFFICIENT BUREAUCRACY IN THE PUBLIC SECTOR FOR SAFE ENVIRONMENT IN ROMANIA - IONESCU, Luminita; ROBERTSON, Kari (Annals of Spiru Haret University. Economic Series, 2016)
Bureaucracy is an important phenomenon in all European countries, with significant consequences over the public and private systems. After the recent economic crises, European governments made efforts to reduce bureaucracy and to speed up the process of absorbing European funds and to encourage the business environment. The aim of this paper is to present some particular aspects of positive bureaucracy and how efficient bureaucracy is facilitating a healthy business sector, a modern public administration and a safe environment in Romania.